Handbook of polymer synthesis, characterization, and processing - Saldivar-Guerra, Enrique; Vivaldo-Lima, Eduardo (Hoboken, New Jersey : John Wiley & Sons, 2013)
'This handbook provides polymer industry professionals and researchers in polymer science and technology a single, comprehensive handbook summarizing all aspects involved in the polymer production chain. Whereas most books deal with polymer science and technology from only one or two aspects, this handbook addresses the major core areas together: polymer synthesis, both from the chemistry and the engineering aspects; polymer characterization, including chemical, physicochemical, rheological properties and others; and polymer processing and transformation into final objects'--
Includes bibliographical references and index.
Keywords: Polymerization